Voluntary Medical Male Circumcision uptake: a concept analysis. - KUSEMWA, Prettyosa M.; TAONATESHE, Takesure; ZVINAVASHE, Mathilda; NDAIMANI, Augustine; MUGADZA, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: Voluntary Medical Male Circumcision (VMMC) uptake is important in the prevention of female to male HIV transmission by 60%. Despite VMMC awareness activities, globally, regionally and locally VMMC uptake remains low. The term VMMC uptake remains without a classic standard definition resulting in different views about the concept. The objective of the article was to define the term uptake in relation to Voluntary Medical Male Circumcision as well as to clarify and assist to come up with standard measurement tool for the concept uptake. Method: This concept paper used Walker & Avant Model of concept analysis (2005). Results: Attributes of VMMC uptake includes: volunteering to get circumcised, getting circumcised, the cost of the procedure, HIV status, knowledge of voluntary medical male circumcision, positive health staff attitudes, in pain, acquiring prescription for analgesia, wound care and abstinence from sex. The proposed definition of VMMC uptake is the willingness to get circumcised in large numbers without coercion when men and boys have adequate knowledge about Voluntary Medical Male Circumcision. The definition will assist in the development of standardised measurement tool to monitor VMMC uptake. Conclusion: The definition of VMMC uptake will facilitate harmonization of voluntary medical male circumcision activities and enhancing clearer understanding of the concept.